Chromobacterium violaceum: A Rare Cause of Urinary Tract Infection - Ujjwal Laghu; Manami Yanagawa; Konosuke Morimoto; Bhim Gopal Dhoubhadel (Case Reports in Infectious Diseases)
A 41-year-old man with a neurogenic bladder due to spinal cord injury (SCI) attended the outpatient department with chief complaints of fever, pain in the lower abdomen, and persistent hematuria for 10 days. From the urine culture and the microbiological and biochemical tests, the causative organism was identified as Chromobacterium violaceum. The isolate was resistant to cephalosporins, while it was sensitive to ofloxacin, gentamicin, and imipenem. Clinicians should be aware of this rare cause of urinary tract infection (UTI), the choice of antibiotic, length of treatment, and necessity of prompt treatment in SCI patients.